posted by Darren on .
Could someone help me solve these system using elementary operations, I am having trouble with both of them.
(For the one above the answer is (-1,-2,3)
(For the one above the answer is (2,4,1)
add all 3 equations --> 2x + y = -4
now add this to the second ...
3x = -3
x = -1
sub that onto the second and third to get y and z
"play around" with the second question in a similar way.
I would use substitution,
e.g. for the first ---> y = 2x
from the second z = 2y - 7
z = 2(2x) - 7
= 4x - 7
now in the third
2z - x = 0
2(4x-7) - x = 0
7x = 14
x = 2
Now you can find the other two.